Splicing-coupled 3′ end formation requires a terminal splice acceptor site, but not intron excision - Davidson, Lee (Oxford University Press, 2013)
Splicing of human pre-mRNA is reciprocally coupled to 3′ end formation by terminal exon definition, which occurs co-transcriptionally. It is required for the final maturation of most human pre-mRNAs and is therefore important to understand. We have used several strategies to block splicing at specific stages in vivo and studied their effect on 3′ end formation. We demonstrate that a terminal splice acceptor site is essential to establish coupling with the poly(A) signal in a chromosomally integrated β-globin gene. This is in part to alleviate the suppression of 3′ end formation by U1 small nuclear RNA, which is known to bind pre-mRNA at the earliest stage of spliceosome assembly. Interestingly, blocks to splicing that are subsequent to terminal splice acceptor site function, but before catalysis, have little observable effect on 3′ end formation. These data suggest that early stages of spliceosome assembly are sufficient to functionally couple splicing and 3′ end formation, but that on-going intron removal is less critical.